Virtual reality in managing Complex Regional Pain Syndrome (CRPS): a scoping review - Arcos-Holzinger, Mauricio; Biebl, Johanna Theresia; Storz, Claudia; Gutmann, Marcus; Azad, Shahnaz Christina; Holzapfel, Boris Michael; Kraft, Eduard (Frontiers in Neurology, 2023)
Background Complex Regional Pain Syndrome (CRPS) is a severe pain disorder that does not yet have a specific treatment. Patients with CRPS not only suffer from a wide range of symptoms that affect their quality of life but also present psychological affections to the way they see their body and specifically their affected limb. Virtual Reality (VR) modalities have become a targeted treatment for chronic pain and in the case of CRPS, may be a valuable approach to the mechanisms that affect these patients. Objectives Using the PRISMA Scoping Review guidelines, we intend to uncover the key information from the studies available about VR modalities in the treatment of CRPS. We focus on the improvement of pain levels, body perception disturbances (BPD), and limb movement/daily function. Results Our search strategy resulted in 217 articles from PubMed. Twenty were assessed for eligibility and seven were included in the final qualitative synthesis. Of these seven articles, we included a clinical trial, three pilot studies, a blinded randomized controlled trial, a crossover double-blind trial, and a randomized controlled trial. These studies provide important subjective patient findings, along with some statistically significant results in the experiences of VR therapies modulating pain, BPD, and improving limb movement/daily function. However, not all the studies included statistical analysis, and there are contradicting data found from some patients that did not perceive any improvement from VR therapies. Conclusions We describe the results found in 7 articles that focus on the treatment of CRPS with VR modalities. Overall, the articles have various limitations, but the strategies related to immersive virtual reality, cardiac signaling, body switching and limb modulation have shown the most promising results for pain reduction and BPD improvement. These strategies reflect on pathophysiological mechanisms that are hypothesized to be affected in CRPS patients leading to the chronic pain and BPD that they experience. Not much evidence was found for improvement in limb movement and daily function. This review is a pathway for future studies on this topic and a more extensive data synthesis when more information is available.